Middle East respiratory syndrome coronavirus: risk factors and determinants of primary, household, and nosocomial transmission. Issue 8 (August 2018) - Hui, David S; Azhar, Esam I; Kim, Yae-Jean; Memish, Ziad A; Oh, Myoung-don; Zumla, Alimuddin
Summary: Middle East respiratory syndrome coronavirus (MERS-CoV) is a lethal zoonosis that causes death in 35·7% of cases. As of Feb 28, 2018, 2182 cases of MERS-CoV infection (with 779 deaths) in 27 countries were reported to WHO worldwide, with most being reported in Saudi Arabia (1807 cases with 705 deaths). MERS-CoV features prominently in the WHO blueprint list of priority pathogens that threaten global health security. Although primary transmission of MERS-CoV to human beings is linked to exposure to dromedary camels ( Camelus dromedarius ), the exact mode by which MERS-CoV infection is acquired remains undefined. Up to 50% of MERS-CoV cases in Saudi Arabia have been classified as secondary, occurring from human-to-human transmission through contact with asymptomatic or symptomatic individuals infected with MERS-CoV. Hospital outbreaks of MERS-CoV are a hallmark of MERS-CoV infection. The clinical features associated with MERS-CoV infection are not MERS-specific and are similar to other respiratory tract infections. Thus, the diagnosis of MERS can easily be missed, unless the doctor or health-care worker has a high degree of clinical awareness and the patient undergoes specific testing for MERS-CoV. The largest outbreak of MERS-CoV outside the Arabian Peninsula occurred in South Korea in May, 2015, resulting in 186 cases with 38 deaths. This outbreak was caused by a traveller with undiagnosed MERS-CoV infection who became ill after returning to Seoul from a trip to the Middle East. The traveller visited several health facilities in South Korea, transmitting the virus to many other individuals long before a diagnosis was made. With 10 million pilgrims visiting Saudi Arabia each year from 182 countries, watchful surveillance by public health systems, and a high degree of clinical awareness of the possibility of MERS-CoV infection is essential. In this Review, we provide a comprehensive update and synthesis of the latest available data on the epidemiology, determinants, and risk factors of primary, household, and nosocomial transmission of MERS-CoV, and suggest measures to reduce risk of transmission.